Genetic evolution of the alpaca in the southern Peruvian Andes - Bustinza Choque, A. Víctor (2023)
The aim of this study was to show the progress of the genetic improvement of the alpaca that inhabits the southern part of Peru, especially in the production of fibre, considering the negative statements. The written literature developed during the last century was reviewed and analysed. First, the variations in alpaca breeding techniques in the periods of the Inca, Viceroyalty and Republican times were reviewed. Then the concepts and criteria of breeding and selection practiced in southern Peru on alpacas were reviewed (first in the communities, then the farms, cooperatives, medium-sized farms and public and private institutions for the production of fibre with the influence of the textile market international). In the third part, the population changes of the Suri and Huacaya breeds and the change in fibre fineness and fleece colour preference were analysed. Likewise, the fineness data of alpaca fibre analysed in the 70s is contrasted with recent work in national fibre laboratories. Finally, the genetic gain in fibre fineness by breeds and generations was determined. It is concluded that there were no changes in the breed populations, but there have been strong changes in the colour of the alpaca fleece towards white and in fineness, whose estimated genetic gain is considerable in favour of the fine fibre, more in Huacaya than in the Suri breed on alpacas of southern Peru.